Double Burden of Nutritional Disorders amongst Adolescents and Strategies required for combating it - Kapil, Umesh; Sareen, Neha (Indian Journal of Community Health, 2015)
Adolescents are the future generation of any country and their nutritional needs are critical for the well being of the society. In India, approximately 20% of the population consists of adolescents (1). Presently, the dietary inadequacy exists due to poverty and it is the main cause of under-nutrition. However simultaneously, we have affluent population groups, which have high consumption of foods rich in fats and calories, leading to over-nutrition and obesity. Thus, India is facing double burden of Nutritional disorders amongst adolescent in which we have under-nutrition at one end of the socio-economic spectrum and over-nutrition at the other (1).